Mobile health (mHealth) interventions for health promotion during the perinatal period in India: a scoping review - Small, Zara; Thompson, Sophie Elizabeth; Sharma, Ankita; Majumdar, Sreya; Thout, Sudhir Raj; Praveen, Devarsetty; Hirst, Jane Elizabeth (Frontiers in Global Women's Health, 2024)
IntroductionPerinatal and maternal mortality rates remain high in India compared to global levels, and there is significant heterogeneity in outcomes across Indian states. Many mobile health (mHealth) interventions have been developed to improve maternal and infant health outcomes in India, however it is unclear how mHealth can best support women in this culturally and resource diverse setting. Therefore, we aimed to identify mHealth interventions targeting women and their families in the perinatal period in India, identify barriers and facilitators to their uptake, and future research directions.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Joanna Briggs Institute guidelines for scoping reviews was used for study selection and screening and the mHealth evidence reporting and assessment checklist was used for evaluating mHealth interventions. PubMed, CINAHL, Global Health, and ACM digital library were searched for records up to 2 April 2023. Studies were included where women who were pregnant, planning for a child, or in the 12 months after delivery, and their families, living in India received health advice via a technological medium.Results1,783 records were screened, 29 met the inclusion criteria, describing 22 different mHealth interventions. Most frequent behavioural targets for interventions were breastfeeding, antenatal nutrition, and infant healthcare. Most interventions communicated to women through one-way communication methods, most frequently SMS. Participants reported positive views of mHealth, reported facilitators included group communication, use of non-maternal informative content, and a pictorial information format. Reported barriers included household responsibilities, technical difficulties, difficulty accessing a phone and difficulty understanding, or misinterpreting messages.DiscussionWe conclude that mHealth interventions are acceptable to women in India during the perinatal period. However, current interventions lack evidence of long term behavioural change and fail to report on features important in sustainability and scalability, namely network infrastructure, data security and interoperability. We propose the need for a framework to understand existing cultural beliefs and support structures to avoid early intervention failure. Future research should investigate multimodal mHealth interventions for behavioural change, identify the appropriate frequency and format of mHealth messages, and address access limitations such as shared mobile phone ownership, and illiteracy rates.